Chitosan/Sodium Alginate/Velvet Antler Blood Peptides Hydrogel Promotes Diabetic Wound Healing via Regulating Angiogenesis, Inflammatory Response and Skin Flora - Hao M; Ding C; Sun S; Peng X; Liu W (Dove Medical Press, 2022)
Mingqian Hao,1,2,* Chuanbo Ding,1,* Shuwen Sun,2 Xiaojuan Peng,2 Wencong Liu2 1College of Traditional Chinese Medicine, Jilin Agricultural Science and Technology College, Jilin, People's Republic of China; 2School of Chinese Medicinal Materials, Jilin Agricultural University, Changchun, People's Republic of China*These authors contributed equally to this workCorrespondence: Chuanbo Ding, College of Traditional Chinese Medicine, Jilin Agricultural Science and Technology College, Jilin, 132109, People's Republic of China, Tel +8615948721648, Email chuanboding0506@163.com Wencong Liu, School of Chinese Medicinal Materials, Jilin Agricultural University, Changchun, 130118, People's Republic of China, Tel +8613804460499, Email jwlw6803@126.comBackground: Diabetic ulcer remains a clinical challenge due to impaired angiogenesis and persistent inflammation, requiring new alternative therapies to promote tissue regeneration.Purpose: In this study, chitosan/sodium alginate/velvet antler blood peptides (CS/SA/VBPs) hydrogel (CAVBPH) was fabricated and used in the treatment of skin wounds in type 2 diabetes mellitus (T2D) for the first time.Methods: VBPs were prepared by hydrolysis and ultrafiltration, and their sequences were identified using LC-MS/MS. The CAVBPH was further fabricated and characterized. A mouse model of T2D was induced by a high-sugar and high-fat diet (HSFD) and streptozotocin (STZ) injection. CAVBPH was applied topically to T2D wounds, and its effects on skin repair and potential biological mechanisms were analyzed by appearance observation, histopathological staining, bioinformatics analysis, Western blot, and 16S rRNA sequencing.Results: VBPs had numerous short-chain active peptides, excellent antioxidant activity, and a low hemolysis rate. CAVBPH exhibited desirable biochemical properties and participated in the diabetic wound healing process by promoting cell proliferation (PCNA and α-SMA) and angiogenesis (capillaries and CD31) and alleviating inflammation (CD68). Mechanistically, the therapeutic effect of CAVBPH on chronic wounds might rely on activating the PI3K/AKT/mTOR/HIF-1α/VEGFA pathway and reversing the expression of inflammatory cytokines TNF-α and IL-1β. The results of 16S rRNA sequencing indicated that T2D significantly altered the diversity and structure of skin flora at the wound site. CAVBPH treatment elevated the relative abundance of beneficial microbes (e.g., Corynebacterium_1 and Lactobacillus) and reversed the structural imbalance of skin microbiota.Conclusion: These results indicate that CAVBPH is a promising wound dressing, and its repair effect on diabetic wounds by regulating angiogenesis, inflammatory response, and skin flora may depend on the rich small peptides in VBPs.Keywords: velvet antler blood peptides, diabetic wound, hydrogel, bioinformatics, skin flora